On the characterization and evaluation of residential on-site E-car-sharing. (1st May 2022) - Corinaldesi, Carlo; Lettner, Georg; Auer, Hans
Abstract: E-car-sharing concepts can play a key role in future urban areas as a new and sustainable transport system. When it comes to residential buildings, the added values of sharing systems are reduced parking space and increased use of solar photovoltaics generation on-site. This work proposes a simple and complete method to define residential building tenants' optimal investment and operation, switching from car ownership to an e-car-sharing system. A mixed-integer linear optimization framework describes technologies such as battery storages, solar photovoltaics, electric vehicles, and charging stations. Furthermore, different scenarios are defined and simulated in order to investigate and evaluate the economic potential of residential on-site e-car-sharing. It is shown that with the actual grid tariff design in Austria, the integration of bidirectional charging stations is not cost-effective if considering only the Day-Ahead spot market. The results show that integrating an e-car-sharing system in a residential building allows for fewer cars and charging stations with higher nominal power, reducing the annual total costs of the residential building tenants by up to 29%. On the other hand, the results indicate that e-car-sharing systems can also lead to lower optimal installed solar photovoltaic power. Highlights: A mathematical method is defined to determine the optimal operation of shared EVs. Representation of multiple technologies with the exclusive use of linear equations. Application of the methods to an Austrian case study. A cost-benefit analysis for different scenarios is performed.